Perancangan Desain UI/UX Untuk Situs Web Interaktif Dalam Pengenalan Kain Tenun Khas Tradisional Di Bali Menggunakan Metode Prototype - Maharani, Ni Made Sintha; I Kadek Noppi Adi Jaya; I kadek Andy Asmarajaya (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2026)
In the digital era, the preservation of local culture faces both challenges and opportunities. One of the cultural heritages that requires attention is traditional Balinese woven fabric, which holds high historical, aesthetic, and philosophical values but remains relatively unknown among the younger generation. This study aims to design an interactive and educational User Interface (UI) and User Experience (UX) for a website dedicated to introducing and marketing traditional Balinese woven fabrics. The approach is expected to bridge traditional values with modern digital habits, while fostering cultural appreciation through digital media. This research adopts the prototype method, with the UI/UX design developed using Figma and evaluated using the System Usability Scale (SUS) questionnaire. The test results from 41 respondents yielded a SUS score of 70, which is above the global average score of 68, indicating that the design falls within the “Good” or “Acceptable” category. The resulting website design not only facilitates product transactions but also provides educational information about the creation process and cultural values embedded in the fabrics. Therefore, the developed UI/UX design is expected to serve as a digital solution for preserving Balinese woven fabrics and increasing young people’s engagement with local cultural heritage.